Sestrin2, a Regulator of Thermogenesis and Mitohormesis in Brown Adipose Tissue - Ro, Seung-Hyun; Semple, Ian; Ho, Allison; Park, Hwan-Woo; Lee, Jun Hee (Frontiers in Endocrinology, 2015)
Sestrin2 is a stress-inducible protein that functions as an antioxidant and inhibitor of mTOR complex 1. In a recent study, we found that Sestrin2 overexpression in brown adipocytes interfered with normal metabolism by reducing mitochondrial respiration through the suppression of uncoupling protein 1 (UCP1) expression. The metabolic effects of Sestrin2 in brown adipocytes were dependent on its antioxidant activity, and chemical antioxidants produced similar effects in inhibiting UCP1-dependent thermogenesis. These observations suggest that low levels of reactive oxygen species (ROS) in brown adipocytes can actually be beneficial and necessary for proper metabolic homeostasis. In addition, considering that Sestrins are ROS inducible and perform ROS detoxifying as well as other metabolism-controlling functions, they are potential regulators of mitohormesis. This is a concept in which overall beneficial effects result from low-level oxidative stress stimuli, such as the ones induced by caloric restriction or physical exercise. In this perspective, we incorporate our recent insight obtained from the Sestrin2 study toward a better understanding of the relationship between ROS, Sestrin2, and mitochondrial metabolism in the context of brown adipocyte physiology.